REPRESENTASI KORUPSI DALAM NOVEL-NOVEL INDONESIA ERA REFORMASI - Kasmuri Kasmuri (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2017)
The purpose of this study is to describe the representation of corruption in Indonesian novels of reform era. This study used descriptive qualitative method. This research data is in the form of phrase, sentence, paragraph in novel 86 works of Okky Madasari and novel Slank 5 Hero from Atlantis by Sukardi Rinakit. Data collection techniques include documentation techniques, refer to, and record. Data analysis techniques use these steps: reading novels, taking data, analyzing data, summarizing, and compiling reports. The results of this study can be concluded that in novel 86 and novel Slank 5 Hero from Atlantis there are forms of corruption include bribe bribery, extortion, and cheating. Factors causing corruption include internal factors and external factors.